Analisis Hubungan Antara Pertumbuhan Ekonomi dan Tingkat Pengangguran di Indonesia - Juwita Handayani; Abdul Latif Lubis; Makhrani Makhrani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the relationship between economic growth and the unemployment rate in Indonesia during the period of 2010 to 2023. The main issue addressed is whether national economic growth significantly affects the reduction of unemployment. This research employs a quantitative approach using simple linear regression analysis and relies on secondary data obtained from Statistics Indonesia (Badan Pusat Statistik – BPS). The results reveal a significant negative relationship between economic growth and the unemployment rate. The regression coefficient of -0.32 indicates that a 1% increase in economic growth is associated with a 0.32% decrease in the unemployment rate. The R-squared value of 0.45 suggests that economic growth explains 45% of the variation in unemployment, while the remaining 55% is influenced by other factors such as skill mismatches, the informal sector structure, and the quality of education. These findings support Okun’s Law and align with economic literature stating that economic growth has the potential to generate employment opportunities. However, its effectiveness depends on the structure of the economy and labor market policies. It is therefore concluded that economic growth must be accompanied by inclusive and employment-oriented policies to optimally reduce unemployment in Indonesia.